2016
DOI: 10.2166/ws.2016.146
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutrient supplementation on DOC removal in drinking water biofilters

Abstract: Analysis of the impacts of nitrogen, phosphorus and potassium supplementation on biofilter performance for organic carbon removal was studied on laboratory-scale biofilter columns. Three dual media biofilter columns were fed with synthetic raw water C:N:P ratios of 546:24:1, 100:10:1, and 25:5:1 (w/w) to simulate nutrient limited and two nutrient supplemented conditions, respectively. Research found that air-scour versus water only backwash improved the nutrient limited dissolved organic carbon (DOC) removal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Literature indicates that the microbial activity correlates with the availability of nutrients, i.e., the content of carbon, nitrogen, and phosphorus in the water flowing into the biosorption field. The C:N:P ratio should be 100:10:1 and deficiency of any of the constituents limits the growth and development of microorganisms, thus interfering with the course of the biodegradation process [39,40]. Dhawan et al controlled the effectiveness of three biofilters in which the treated water differed in terms of nutrient content as follows: 546:24:1, 100:10:1, and 25:10:1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature indicates that the microbial activity correlates with the availability of nutrients, i.e., the content of carbon, nitrogen, and phosphorus in the water flowing into the biosorption field. The C:N:P ratio should be 100:10:1 and deficiency of any of the constituents limits the growth and development of microorganisms, thus interfering with the course of the biodegradation process [39,40]. Dhawan et al controlled the effectiveness of three biofilters in which the treated water differed in terms of nutrient content as follows: 546:24:1, 100:10:1, and 25:10:1.…”
Section: Discussionmentioning
confidence: 99%
“…Dhawan et al controlled the effectiveness of three biofilters in which the treated water differed in terms of nutrient content as follows: 546:24:1, 100:10:1, and 25:10:1. The Dissolved Organic Carbon (DOC) removal efficiency was 23.5%, 28.6%, and 33.5% respectively [40]. In the case of waters containing natural organic matter and inorganic nitrogen, phosphate ions are essential [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…However, in some cases it was found that microbial growth in drinking water was limited by phosphorus [18][19][20][21] or nitrogen [13] instead of carbon. Dhawan et al [22] investigated the influence of nutrient supplementation on DOC removal by BAC filters by testing different types of ratios. Increased nutrient concentrations beyond the typical ratio of 100:10:1, resulted in increased removal of DOC.…”
Section: Introductionmentioning
confidence: 99%
“…Although researchers have tried to find correlations between biomass development and the observed biodegradation in the BAC filters under varying operating conditions, no clear correlations have been found [14,22]. This underlines the complexity of the processes taking place in the BAC filters.…”
Section: Introductionmentioning
confidence: 99%
“…According to LeChevallier et al (1999), for optimal biofiltration performance a C:N:P ratio of 39:4.5:1 on a weight basis is required. Under nutrient rich conditions, authors have reported improvement in organics removals (Dhawan, et al 2017. .…”
Section: Figure 5 -6 Doc Removals Through the Biofilters For Differinmentioning
confidence: 99%